(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The present study had the objective of verifying the relationships among the self-reports produced by three behavior therapists (with differing length of professional experience) about their own behavior when interacting with their patients and the respective behavior that in fact occurred. Nine sessions were filmed and transcribed in full. Seven days after the session, a questionnaire was handed out; only in the third session did the therapists attend the filming before the interview. The basis for the categories of analysis was the verbal operant known as tact. Therapist A presented the highest indices of distortion in the self-reports, followed by Therapist B: both presented frequencies of unstable performances; Therapist C presented the lowest indices of distortion and the most steady performance, and was the only one that stated that he did not remember what occurred during the session. The results corroborate the behavioral analysis theory: Self-reports about past events tend to be imprecise.